Cottonmouth [large type] - Lynch, Sean, active 2013- (Lynch, Sean Guns of Samuel Pritchard., 2020)
"A legendary gunfighter can never outrun the ghosts of his past. But he can outshoot them. Acclaimed author Sean Lynch's epic saga of Samuel Pritchard continues-with a venegance. 1874. After losing his innocence in the Civil War and risking his life as a Texas Ranger, Samuel Pritchard has finally settled into a peaceful life in his hometown of Atherton, Missouri. As marshall, he hopes to put his bloody past behind him. To see his sister marry his lifelong friend. To find a wife and raise a family. For the first time in his life, Pritchard isn't gunning for anyone-and no one is gunning for him. Or so he thinks. Strangers have arrived in Atherton. Hard-eyed men with guns. Someone has placed a bounty on Pritchard's head: $10,000 in gold, deposited anonymously in a Wells Fargo bank, payable to anyone who puts the legendary pistolero in a pine box. This is the story of Samuel Pritchard. A small-town sheriff with a larger-than-life reputation, lightning-fast guns, and a long list of enemies who'd love to see him dead"--Provided by publisher.